Digital Hybridity and Ecological Advocacy in Wayang Motekar as a Cultural Communication Strategy - Atalia Praratya; Diah Sri Rejeki; Ibrahim Adi Surya; Della Dwinanti Sumpena (INJECT (Interdisciplinary Journal of Communication), 2026)
Traditional Indonesian performing arts have faced the challenge of low youth participation in the digital era, raising questions about cultural continuity. This research investigates the application of strategic communication to contemporary Wayang Motekar, a modernist version of Sundanese puppet theatre through which traditional cultural messages are conveyed to digital-native participants. The data were collected through 14 semi-structured interviews (with creators, production teams, cultural observers, and audiences), 8 live performances, and a systematic analysis of digital material from YouTube and Instagram. Three interlinked strategic dimensions were identified. 1) Message planning or the strategic recontextualization of environmental philosophy, which was framed in Sundanese as part of contemporary sustainability discourse, 2) media selection that included video-mapping, projection systems, and platform-differentiated digital distribution; and 3) participatory delivery methods focusing on aesthetic-emotional co-creation rather than didactic instruction. This successful process of cultural communication is facilitated by symbolic-aesthetic involvement, multimodal translation between media platforms, and the positioning of the audience as super-active sense-makers, strategically moving strategic communication theorizing from organization to the sphere of cultural performance. While Wayang Motekar has succeeded in presenting traditional arts as contemporary and can be accepted by the younger generation, it is a matter of fact that success depends on the capability of digital technology literacy among youths, the availability of digital infrastructures, and socio-economic conditions. The study develops an overarching theoretical framework that conceptualizes aesthetic hybridity as instrumental communication, which allows for the empirical identification of the persistence of traditional modes of knowledge, considering digital change.